Comparative genomic analysis of azasugar biosynthesis - Hailey E. Beal; Nicole A. Horenstein (AMB Express, 2021)
Abstract Azasugars are monosaccharide analogs in which the ring oxygen is replaced with a nitrogen atom. These well-known glycosidase inhibitors are of interest as therapeutics, yet several aspects of azasugars remain unknown including their distribution, structural diversity, and chemical ecology. The hallmark signature of bacterial azasugar biosynthesis is a three gene cluster (3GC) coding for aminotransferase, phosphatase, and dehydrogenase enzymes. Using the bioinformatics platform Enzyme Similarity Tool (EST), we identified hundreds of putative three gene clusters coding for azasugar production in microbial species. In the course of this work, we also report a consensus sequence for the aminotransferase involved in azasugar biosynthesis as being: SGNXFRXXXFPNXXXXXXXLXVPXPYCXRC. Most clusters are found in Bacillus and Streptomyces species which typically inhabit soil and the rhizosphere, but some clusters are found with diverse species representation such as Photorhabdus and Xenorhabdus which are symbiotic with entomopathogenic nematodes; the human skin commensal Cutibacterium acnes, and the marine Bacillus rugosus SPB7, a symbiont to the sea sponge Spongia officinalis. This pan-taxonomic survey of the azasugar 3GC signature may lead to the identification of new azasugar producers, facilitate studies of their natural functions, and lead to new potential therapeutics.